Analysis of students’ mathematical reasoning between different genders: A systematic literature review - Rahmat Kusharyadi; Dadang Juandi (Universitas Sarjanawiyata Tamansiswa, 2023)
The main purpose of this study was to examine existing studies related to mathematical reasoning skills based on gender differences using Systematic Literature Review (SLR). The following studies identify reasoning abilities based on gender differences. The review was carried out by carrying out several stages, namely the process of identification, screening, feasibility, inclusion, and data analysis on two livelihood machines, namely SCOPUS and ERIC. In reporting this study, the guidelines used were PRISMA guidelines. The data used was sorted by the specified criteria and this resulted in a total of 8 articles. Our findings identify that the study was conducted in three places: Indonesia, Sweden, and Turkey. Based on the findings of the study using three research designs, namely qualitative, mixed method, and quasi-experimental. The topics of the material used in this study are topics of geometry, algebra, and other branches of mathematics. The SLR also includes characteristics of reasoning abilities found by gender as well as the distribution of studies in terms of trends and countries.